Training of future primary school teachers for work in an understaffed school - Omirzakova, Assel; Abildina, Sаltanat; Baimaganbetova, Zhuldyzay; Amzeyeva, Gulnara; Sherimova, Aliya (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study examined the emotional and psychological environments of primary school students and the role of teachers in maintaining their health. The goal was to understand how the educational environment affects students’ physical, psycho-emotional, and social health and to develop methods for training future primary school teachers to support student well-being. The study involved 105 future teachers from Karaganda Buketov University, Republic of Kazakhstan, selected through convenience sampling. The scale emotional response test by Mehrabyan and Epstein was used to assess empathic abilities. The results showed that 16% of participants had high empathy, 37% had average empathy, and 47% had low empathy. The findings highlight the need for enhanced empathy training and health-promoting environments in schools. Practical implications include incorporating empathy modules in teacher education programs and investing in ergonomic infrastructure to improve student well-being and academic achievement.